Stimulation of Caveolin-1 Signaling Improves Arteriovenous Fistula Patency. Issue 4 (April 2019) - Hashimoto, Takuya; Isaji, Toshihiko; Hu, Haidi; Yamamoto, Kota; Bai, Hualong; Santana, Jeans M.; Kuo, Andrew; Kuwahara, Go; Foster, Trenton R.; Hanisch, Jesse J.; Yatsula, Bogdan A.; Sessa, William C.; et al.
Abstract : Objective—: Arteriovenous fistulae (AVF) are the most common access created for hemodialysis; however, many AVF fail to mature and require repeated intervention, suggesting a need to improve AVF maturation. Eph-B4 (ephrin type-B receptor 4) is the embryonic venous determinant that is functional in adult veins and can regulate AVF maturation. Cav-1 (caveolin-1) is the major scaffolding protein of caveolae—a distinct microdomain that serves as a mechanosensor at the endothelial cell membrane. We hypothesized that Cav-1 function is critical for Eph-B4–mediated AVF maturation. Approach and Results—: In a mouse aortocaval fistula model, both Cav-1 mRNA and protein were increased in the AVF compared with control veins. Cav-1 KO (knockout) mice showed increased fistula wall thickening ( P =0.0005) and outward remodeling ( P <0.0001), with increased eNOS (endothelial NO synthase) activity compared with WT (wild type) mice. Ephrin-B2/Fc inhibited AVF outward remodeling in WT mice but not in Cav-1 KO mice and was maintained in Cav-1 RC (Cav-1 endothelial reconstituted) mice (WT, P =0.0001; Cav-1 KO, P =0.7552; Cav-1 RC, P =0.0002). Cavtratin—a Cav-1 scaffolding domain peptide—decreased AVF wall thickness in WT mice and in Eph-B4 het mice compared with vehicle alone (WT, P =0.0235; Eph-B4 het, P =0.0431); cavtratin also increased AVF patency (day 42) in WT mice ( P =0.0275). Conclusions—: Endothelial Cav-1 mediates Eph-B4–mediated AVF maturation. The Eph-B4-Cav-1 axis regulates adaptive remodeling during venous adaptation to the fistula environment. Manipulation of Cav-1 function may be a translational strategy to enhance AVF patency. Abstract : Supplemental Digital Content is available in the text.